1978
DOI: 10.1002/cpt1978232165
|View full text |Cite
|
Sign up to set email alerts
|

Biological determinants of propranolol disposition in man

Abstract: Propranolol disposition has been investigated in 15 normal subjects with the use of a protocol which allowed simultaneous determination of the kinetics of the drug after both intravenous and oral administration by giving H3‐propranolol intravenously and native drug orally. In addition, plasma propranolol binding and the bloodlplasma propranolol concentration ratio (B/P) were measured. The data were used to calculate hepatic blood flow as well as systemic drug clearance from the blood and intrinsic clearance, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(49 citation statements)
references
References 14 publications
1
48
0
Order By: Relevance
“…Presumably, altered haemodynamics as a result of a reduction in cardiac output is a major underlying factor. A reduction in hepatic blood flow has been shown to affect the removal rates of lignocaine and propranolol, antiarrhythmic agents whose clearances by the liver are dependent on the rate of blood flow to this organ (Boyes, Adams & Duce, 1970, Stenson, Constantino & Harrison, 1971Nies, Evans & Shand, 1973;Kornhauser, Wood, Vestal, Wilkinson, Branch & Shand, 1978). The effects of decreased intestinal blood flow on reducing the rate of gastrointestinal drug absorption has recently been discussed by Benet etal.…”
Section: Resultsmentioning
confidence: 99%
“…Presumably, altered haemodynamics as a result of a reduction in cardiac output is a major underlying factor. A reduction in hepatic blood flow has been shown to affect the removal rates of lignocaine and propranolol, antiarrhythmic agents whose clearances by the liver are dependent on the rate of blood flow to this organ (Boyes, Adams & Duce, 1970, Stenson, Constantino & Harrison, 1971Nies, Evans & Shand, 1973;Kornhauser, Wood, Vestal, Wilkinson, Branch & Shand, 1978). The effects of decreased intestinal blood flow on reducing the rate of gastrointestinal drug absorption has recently been discussed by Benet etal.…”
Section: Resultsmentioning
confidence: 99%
“…Thus the prolongation in lignocaine half-life which occurs in cardiac failure has been attributed to reduced HBF (Thomson, Rowland & Melmon, 1971), and lignocaine elimination in animals appears to be affected by reduced HBF in the presence of beta blockade (Branch, Shand, Wilkinson & Nies, 1973). In theory HBF would not be expected to alter the bioavailability of drugs with a high excretion ratio (Kornhauser, Wood, Vestal, Wilkinson, Branch & Shand, 1978). However, recent measurements of drug bioavailability in situations of changed HBF have cast doubt on this (Melander, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…After multiple dosing of LA propranolol, mean Cmax was higher than that observed in non cirrhotic subjects (Leahey et al, 1980;Serlin et al, 1983) but near to that previously found in cirrhotic patients (Arthur et al, 1985). The difference may be the consequence of higher degree of accumulation in cirrhotic patients: 4.0 instead of 1.7 to 1.8 in non cirrhotic subjects, (Leahey et al, 1980;Serlin et al, 1983) possibly arising from a reduced first pass effect (Wood et al, 1978b) due to enzyme saturation and/or a slight decrease in hepatic blood flow (Kornhauser et al 1978). The degree of accumulation was greater with LA propranolol than with C propranolol and this has been reported in normal subjects (Leahey et al, 1980).…”
Section: Pharmacokineticsmentioning
confidence: 56%